Exploring Skin Manifestations in Women with Polycystic Ovary Syndrome: A Cross-sectional Analysis. - Savita Pannu Rathi, Punit Pratap, Pravesh Yadav (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Polycystic ovary syndrome (PCOS) is a complex multisystem metabolic disorder thatsignificantly affects fertility and overall quality of life. Cutaneous manifestations suchas acne, hirsutism, androgenetic alopecia,